Nutritional Assessment of individuals interned in a general hospital - Carla de Oliveira Barbosa Rosa; Bárbara Pereira da Silva; Karla Pereira Balbino; Sônia Machado Rocha Ribeiro; Andréia Queiroz Ribeiro; Heloísa Helena Firmino (O Mundo da Saúde)
The evaluation of the nutritional status is important to detect malnourished patients or patients having risk of malnourishment. Malnutrition is associated to a higher risk of infection, metabolic complications, prolonged hospitalizations and morbimortality. The aim in this study was to evaluate the nutritional status of individuals interned in a hospital and compare the measured corporal weight with the weight estimated by formulas. The study was cross-sectional, done during three months with patients admitted in a general hospital by the Health Public Service from Brazil (SUS), health plans or private payment. The nutritional assessment was done in all the individuals admitted in the hospital during the period of study (n = 51), and we did an anthropometric assessment, biochemical analysis and subjective global assessments. Data analysis consisted in frequency distributions and measurements of central tendency and dispersion. Comparisons of means were also done. The results revealed a high prevalence of anemia in the individuals (56.9%); most of them (74.6%) showed leukocytes within the normal range and lymphocytes (65.5%) below the desirable range. The anthropometric assessment identified a great many individuals as having excess of body weight (45.1%). Concerning the subjective global assessment of nutritional status, the majority presented eutrophy (92.2%). It was not observed any difference between body weights assessed and body weights estimated by predictive equations, being this useful for use in bedridden patients. Nutritional assessments performed immediately assisted in identifying patients at nutritional risk or malnourished, allowing the establishment of appropriate nutritional therapy.